The Role of Emotions in Protests against Modernist Urban Redevelopment in Perth and Halifax - Gregory, Jenny; Grant, Jill (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2014)
In the 1950s and 1960s modernist town planning reordered countless cities through urban renewal and freeway-building projects. Applying rational planning expertise generated emotional responses that often lingered long after redevelopment occurred. This article considers the emotional response to urban renewal in two cities advised by the British town planner Gordon Stephenson. In Perth, Australia, Stephenson was amongst a group of experts who planned a freeway that obliterated part of the valued river environment and threatened a historic structure. In Halifax, Stephenson prepared the initial scientific study used to justify dismantling part of the downtown and a historic black community on the urban fringe. While the Perth case generated an explosion of emotional intensity that failed to prevent environmental despoliation but saved some heritage assets, the Halifax example initiated a lingering emotional dispute involving allegations of neglect and racism. Comparing cases resulting from the activities of a noted practitioner illustrates differing emotional trajectories produced in the wake of the modernist planning project.